Accounting Information Systems And Financial Inclusion On The Performance Of MSME’S Through The Quality Of Financial Statements On Small And Medium Enterprises - Meyi Hamzani, Reby (Al-Adzkiya Publisher, 2025)
The purpose of this study was to determine and analyze the effect of accounting information systems and financial inclusion on performance through the quality of financial reports directly or indirectly. The approach used in this study is a causal approach. The population in this study were all MSME actors in the city of Medan. The sample in this study used the slovin formula as many as 95 MSME actors in the city of Medan. The data collection technique in this study used a questionnaire technique. The data analysis technique in this study uses a quantitative approach using statistical analysis by using the Auter Model Analysis test, Inner Model Analysis, and Hypothesis Testing. Data processing in this study using the PLS (Partial Least Square) software program. The results of this study prove that directly the accounting information system, financial inclusion and financial report quality have a significant effect on the performance of MSMEs, accounting information systems and financial inclusion have a significant effect on the quality of financial statements and indirectly the accounting information system and financial inclusion have a significant effect on the performance of MSMEs. through the quality of financial reports of small and medium-sized businesses in the city of Medan